Environmentally friendly glued laminated timber - Šernek, Milan (Anali PAZU, 2022)
Bonding performance of glued laminated timber, which was produced from the heat treated wood and bonded with the adhesive mixture containing different proportions of liquefied wood, was studied. The results of the shear strength of the adhesive bond indicated that the heat treated wood bonded with the adhesive mixture containing liquefied wood can be used as elements for windows. Standard requirements have been fulfilled with the specimens, which were bonded with the adhesive mixture containing 25 % of liquefied wood and 75 % of melamine-urea-formaldehyde adhesive. Novel laminated composites from heat treated wood, bonded with new type of adhesives, represent ecologically friendly products because a part of adhesive was made from natural renewable material – wood. No chemicals were used for the improvement of durability of wood. The increased durability and improved dimensional stability of the wood was achieved by the heat treatment.
Keywords: bonding; wood; melamine-urea-formaldehyde adhesive; liquefied wood; heat treatment